2015
DOI: 10.3390/ijms160613203
|View full text |Cite
|
Sign up to set email alerts
|

The rs2516839 Polymorphism of the USF1 Gene May Modulate Serum Triglyceride Levels in Response to Cigarette Smoking

Abstract: Single nucleotide polymorphisms (SNPs) of the USF1 gene (upstream stimulatory factor 1) influence plasma lipid levels. This study aims to determine whether USF1 SNPs interact with traditional risk factors of atherosclerosis to increase coronary artery disease (CAD) risk. In the present study serum lipid levels and USF1 gene polymorphisms (rs2516839 and rs3737787) were determined in 470 subjects: 235 patients with premature CAD and 235 controls. A trend of increasing triglycerides (TG) levels in relation to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
2
11
0
2
Order By: Relevance
“…Niemiec et al reported that the USF1 rs2516839 polymorphism modified the triglyceride response to smoking, however, triglyceride differences between the CC, CT and TT genotypes were greater in smokers (2.27 ± 0.26, 1.80 ± 0.09, 1.53 ± 0.10 mmol/L, respectively) in accordance with their higher average triglycerides (1.79 ± 0.07 mmol/L) than in nonsmokers (1.49 ± 0.11, 1.46 ± 0.06, 1.57 ± 0.08, respectively) in accordance with their lower concentrations (1.51 ± 0.05 mmol/L) 59 . Ge et al reported that the difference between the CC homozygotes and carriers of the T-allele of CYBA C242T polymorphism was significant in smokers (0.17 mmol/L, P = 0.01) but not nonsmokers (0.04 mmol/L, P = 0.76), which quantile-dependent expressivity would partially attribute to the smokers higher average triglyceride concentrations (1.33 vs. 1.21 mmol/L) 60 .…”
Section: Smokingsupporting
confidence: 68%
See 2 more Smart Citations
“…Niemiec et al reported that the USF1 rs2516839 polymorphism modified the triglyceride response to smoking, however, triglyceride differences between the CC, CT and TT genotypes were greater in smokers (2.27 ± 0.26, 1.80 ± 0.09, 1.53 ± 0.10 mmol/L, respectively) in accordance with their higher average triglycerides (1.79 ± 0.07 mmol/L) than in nonsmokers (1.49 ± 0.11, 1.46 ± 0.06, 1.57 ± 0.08, respectively) in accordance with their lower concentrations (1.51 ± 0.05 mmol/L) 59 . Ge et al reported that the difference between the CC homozygotes and carriers of the T-allele of CYBA C242T polymorphism was significant in smokers (0.17 mmol/L, P = 0.01) but not nonsmokers (0.04 mmol/L, P = 0.76), which quantile-dependent expressivity would partially attribute to the smokers higher average triglyceride concentrations (1.33 vs. 1.21 mmol/L) 60 .…”
Section: Smokingsupporting
confidence: 68%
“…Environmental factors that distinguish higher vs. lower triglycerides (e.g., obesity, physical inactivity, smoking, alcohol, high-carbohydrate diets, T2DM) are predicted to produce different genetic estimates under quantile-dependent expressivity. Traditionally, these differences have been attributed to gene-environment interactions, where: 1) the effect of the genotype on the phenotype differs by environment [26][27][28][29][30][31][32][33][34][35][36][37][41][42][43][45][46][47][48][49][50][51][52][53][54][55][58][59][60][61][62][63][65][66][67][74][75][76][77][78][79][80] , or equivalently: 2) the effect of the environment on the phenotype differs by genotype 36,[38][39][40]44,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natomiast w populacji polskiej Niemiec i wsp. [29] dowiedli, że genotypy USF1 mogą modyfikować stężenie triacylogliceroli i ryzyko rozwoju choroby wieńcowej w odpowiedzi na palenie tytoniu. Analizując genetyczne i środowiskowe czynniki ryzyka, ujawniono, że nosicielstwo allelu C polimorfizmu rs2516839 zwiększa ryzyko choroby wieńcowej u osób palących tytoń względem homozygot TT (model multiplikatywny; SIM = 2,69; 95% CI: 1,21-6,01; p = 0,015).…”
Section: Usf1 W Patologii Wybranych Jednostek Chorobowychunclassified
“…Analizując genetyczne i środowiskowe czynniki ryzyka, ujawniono, że nosicielstwo allelu C polimorfizmu rs2516839 zwiększa ryzyko choroby wieńcowej u osób palących tytoń względem homozygot TT (model multiplikatywny; SIM = 2,69; 95% CI: 1,21-6,01; p = 0,015). Wykazano także związek pomiędzy paleniem tytoniu a wzrostem stężenia TG dodatnio zależny od liczby kopii allelu C [29]. Ponadto ujawniono, że genotyp CC jest związany z ponadnormatywnym stężeniem TG (OR = 1,81; 95% CI: 1,16-2,82; p = 0,008) w odróżnieniu do genotypu TT związanego z obniżonym stężeniem TG (OR = 0,58; 95% CI: 0,32-0,86; p = 0,007).…”
Section: Usf1 W Patologii Wybranych Jednostek Chorobowychunclassified